Die Akademien der Wissenschaften in Zentraleuropa im Kalten Krieg Transformationsprozesse im Spannungsfeld von Abgrenzung und Annäherung - Feichtinger, Johannes (Verlag der Österreichischen Akademie der Wissenschaften, 2018)
During the Cold War, the systemic rivalry between East and West was also carried out in the field of scholarship. This volume examines the Academies of Sciences in Central Europe on either side of the Iron Curtain in the early stages of the Cold War (and in some cases beyond). These include academies in the Socialist states (the Slovenian Academy of Sciences and Arts, the Romanian People's Republic Academy, the Hungarian Academy of Sciences, the Polish Academy of Sciences, the Czechoslovakian Academy of Sciences, and the Slovakian Academy of Sciences), academies in divided Germany (the German Academy of Sciences at Berlin [Academy of Sciences of the GDR], the Saxon Academy of Sciences, the Academy of Agricultural Sciences of the GDR, the Bavarian Academy of Sciences and Humanities, the Heidelberg Academy of Sciences and Humanities, and finally the Leopoldina in Halle/Saale as the all-German Academy of Sciences), and the Austrian Academy of Sciences.Der vorliegende Band ermöglicht erstmals einen vergleichenden Blick auf Akademien der Wissenschaften in Zentraleuropa im Kalten Krieg.